Association between variants of MTHFR genes and psychiatric disorders: A meta-analysis - Zhang, Yu-Xin; Yang, Lu-Ping; Gai, Cong; Cheng, Cui-Cui; Guo, Zhen-yu; Sun, Hong-Mei; Hu, Die (Frontiers in Psychiatry, 2022)
Background: Psychiatric disorders have seriously affected human life, and one of the risk genes related to psychosis is the methylenetetrahydrofolate reductase (MTHFR) gene. Therefore, we performed a meta-analysis to investigate the correlations between two prevalent MTHFR single nucleotide polymorphisms (SNPs), MTHFR C677T and A1298C, and severe psychological disorders (schizophrenia, major depression, and bipolar disorder). Methods: This meta-analysis recruited 81 published studies which were selected by a search of electronic databases up to April 2022. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the association between MTHFR polymorphism and psychiatric disorders susceptibility by using random effect models. Results: We found that MTHFR C677T polymorphism is significantly related with schizophrenia and major depression in the overall population, and MTHFR C677T has been linked to an increased risk of bipolar disorder in the recessive model (TT vs. CT + CC). Ethnic subgroup analysis shows that schizophrenia and major depression are significantly correlated with MTHFR C677T and A1298C in Asian populations, but not in Caucasians. Besides, schizophrenia is significantly correlated with MTHFR C677T in the African population. However, the MTHFR A1298C polymorphism is only marginally linked to major depression. Conclusion: These results indicate that MTHFR may contribute to the common pathogenesis of psychiatric diseases and that its variants may be essential in controlling the expression of psychosis-related genes.